Precarização e divisão sexual do trabalho : particularidades de catadores/as de resíduos sólidos no contexto brasileiro - Melo, Tatiane Cravo de (2021)
The general objective of this research is to analyze and unveil the knowledge produced about the working conditions of solid waste collectors, taking as a reference research linked to Postgraduate courses in Social Work, available in the Coordination's Theses and Dissertations Catalog for the Improvement of Higher Education Personnel (Capes), from 2014 to 2019. The theoretical perspective adopted is based on the historical and dialectical materialist method, to reach the essence, the numerous particularities and “the maximum fidelity in the ideal reproduction of the object under analysis”. When it comes to the investigation process, the research has a qualitative character, involves technical procedures, through documentary and bibliographic research. To obtain data, we consulted the following source: Capes Theses and Dissertations Catalog; and we carried out the mapping of dissertations and theses about solid waste collector workers, linked to the Post-Graduate Stricto Sensu courses in Social Service in Brazil. Through the analyzes carried out, it was detected that in Brazil, during the period from 2014 to 2019, 457 (four hundred and fifty-seven) studies were published on waste pickers. Of these, 100 (one hundred) publications were included in courses composed by the Center for Applied Social Sciences; and 07 were published through Postgraduate courses in Social Work. The survey revealed, at the same time, that in 2019, there were about 800,000 solid waste collectors, of which 70% were female. Professionals who work in the collection and selection of recyclable materials in Brazil are inserted in the modality of informal workers who carry out their activities in unhealthy, inhumane environments and under appalling working conditions. It was observed that in addition to these issues, waste pickers, faced with the capitalist mode of production and reproduction, experience a process of invisibility, prejudice, inequality and social injustice that needs to be demystified and denaturalized.